MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE (TPS) PADA SISWA KELAS VB SD MUHAMMADIYAH I SORONG - Nika Fetria Trisnawati (Qalam : Jurnal Ilmu Kependidikan, 2016)
Abstract This research aims to describe the Cooperative Learning Model Type Think-Pair-Share (TPS) that can improve students' mathematics learning outcomes. The research was conducted in sorong. The subject of this research was fifth grade class B at SD Muhammadiyah I Sorong in academic year 2010/2011. The students consist of 14 males and 24 females. The research was Classroom Action Research (PTK). The procedure and Implementation at the study site was divided into two cycles. In the first cycle performed four times of implementation by using Cooperative Learning Model Type Think-Pair-Share (TPS). The second cycle took four times with the same model. The observations took with the observation sheet has been prepared, and then reflected by writer and teacher to evaluate the research that has been run on each cycle and to improve the implementation of the next cycle. The technique of data collection was done by  using observation and tests. The data were performed with qualitative and quantitative analysis. The results of this study indicate that students' mathematics learning outcomes at SD Muhammadiyah I fifth grade class B increases. At the beginning of test the average was 5,40 and at the end of the first cycle mean score was 5.84. Being at the end of second cycle the average was of 8,09. The action did  to stimulate the students' attention by giving preliminary description of matter at the beginning of the meeting, the student group discussions and presentations, providing competition, growing students’ curiosity by implementing the Cooperative Learning Model Type Think-Pair-Share (TPS). Giving the relevance of study based on students' experience and providing them the example that is relevant to students. To increase the students self confidence was done by giving them the opportunity to answer questions and write them down in front, giving verbal praise who are successful, providing the opportunity to the group to present the result of discussion, and provide feedback. To increase student satisfaction with verbal praise who are successful, notify the student test results obtained, and giving appropriate rewards and not excessive.